2006
DOI: 10.1111/j.1553-2712.2006.tb01695.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment of Acute Respiratory Infections in Acute Care Settings

Abstract: Acute care settings are important targets for reducing inappropriate antibiotic prescribing. The mechanisms accounting for lower antibiotic prescription rates observed with housestaff-associated visits merit further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…In two studies from the United States, antibiotics were prescribed to more than 80% of patients with AECOPD [Lindenauer et al 2006;Gonzales et al 2006] and in a study from Australia, the antibiotic prescribing rate reached 87% [Pretto et al 2012]. Miravitlles and colleagues found that Spanish GPs prescribed antibiotics to 89% of patients with AECOPD [Miravitlles et al 1999].…”
Section: Discussionmentioning
confidence: 99%
“…In two studies from the United States, antibiotics were prescribed to more than 80% of patients with AECOPD [Lindenauer et al 2006;Gonzales et al 2006] and in a study from Australia, the antibiotic prescribing rate reached 87% [Pretto et al 2012]. Miravitlles and colleagues found that Spanish GPs prescribed antibiotics to 89% of patients with AECOPD [Miravitlles et al 1999].…”
Section: Discussionmentioning
confidence: 99%
“…67 Antibiotic prescribing practices were generally similar between seven VA and seven non-VA emergency departments; however, in the three cities in which prescription rates were not comparable between VA and non-VA sites, VA sites had much higher rates of antibiotic prescriptions. 68 Availability of Services. The structure of women's health care differed at eight VA women's health centers and 13 Department of Health and Human Services Centers of Excellence.…”
Section: Safetymentioning
confidence: 99%
“…Emergency providers are often cited as the worst offenders of the overuse of antibiotics [10]. Reasons given for these cited differences include: patients in the ED may be worse, may be less likely to have insurance, may lack access to good medical follow-up, and may have different expectations regarding the need and desire for antibiotics than those in primary care [11].…”
Section: Introductionmentioning
confidence: 99%